Dynamics of fungal growth in stored grain - Hamer, Alison (Cranfield University, 1993)
Large and small-scale respirometry apparatus were developed and optimised to measure the respiration of 25 g and 10 kg seed samples stored under a range of environmental conditions, from 0.80 to 0.95 water activity (~) and 15 to 35°C in all combinations. Respiration of wheat and barley grains was greater, than that of rapeseed and linseed. Oxygen consumption was linear with time for naturally contaminated wheat grain over the range 0.90-0.95 aw/15- 25°C and 0.80-0.95 ~/30-35°C, in sterile wheat grain at 0.90 ~125°C, and in barley and rapeseed at 0.90 ~120°C but was non-linear in wheat grain at 0.80-0.85 ~/15-25°C, linseed at 0.88 ~120°C and in autoclaved, reinoculated wheat grain. Respiration of naturally contaminated wheat grain was determined over the whole range of environmental conditions. Oxygen consumption increased with water activity and temperature. Respiration was comparable whether measured from 25 g or 10 kg samples, allowing the data to be suitable for mathematical modelling. Respiratory quotients (RQ) were generally < 1.0 and closest to 1.0 at 0.95 aw120-35°C but at 15°C they exceeded 1.0 and were closest to 1.0 at 0.80 aw • Respirometry was more sensitive than direct weighing for determining dry matter loss (DML) because fungal biomass was not measured. DML values associated with visible moulding, as calculated by oxygen consumption by wheat and barley, were smaller than those considered acceptable for safe storage. During 7 days storage at 0.85 ~125°C and 0.90 aw/15°C, conditions usually regarded as safe for short term storage, visible moulding and germination loss occurred with, respectively, as little as 0.130% and 0.085% DML. A dose of 10 kGy gamma-radiation destroyed all fungal contamination from wheat grain without affecting percentage germination, although seed vigour and respiration were decreased. Using a new dry spore inoculation method, it was shown that Eurotium amstelodami caused more DML in autoclaved than Penicillium aurantiogriseum over 28 days at 0.85-0.90 ~120°C.